2014
DOI: 10.1179/1743278214y.0000000189
|View full text |Cite
|
Sign up to set email alerts
|

Coupled analysis of mechanical- and corrosion-related degradation of carbon steel spent fuel container

Abstract: Failure of high level waste/spent fuel containers is most likely to occur as a result of mechanical overload following a period of corrosion that results in a reduction of the wall thickness and/or the degradation of the material properties. There can be significant interaction between the mechanical loads and the corrosion processes to which a disposal container is subjected which, in turn, can influence the mode and time of failure. Here, these interactions are illustrated for a single shell, carbon steel sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…These porosity changes are poorly understood in terms of mechanical behavior and also regarding changes to the transport properties at the interface. Numerical codes are able to treat the latter point (Xie et al, 2015) and some coupling between reactive transport codes and mechanical codes exist (e.g., Rutqvist and Tsang, 2002;King et al, 2014a), however this remains a challenge from both the numerical and experimental point of view. …”
Section: Conclusion: What Is Known and What Needs To Be Improvedmentioning
confidence: 99%
“…These porosity changes are poorly understood in terms of mechanical behavior and also regarding changes to the transport properties at the interface. Numerical codes are able to treat the latter point (Xie et al, 2015) and some coupling between reactive transport codes and mechanical codes exist (e.g., Rutqvist and Tsang, 2002;King et al, 2014a), however this remains a challenge from both the numerical and experimental point of view. …”
Section: Conclusion: What Is Known and What Needs To Be Improvedmentioning
confidence: 99%
“…[7,9,14] Hydrogen-induced cracking (HIC) is treated in two different ways in safety cases. In some programmes (Table 2a), the possibility of HIC is quantitatively assessed by comparing the time-dependent absorbed H concentration and the associated stress-intensity factor K I for a potentially critical defect with a critical K I (either the threshold K th for subcritical crack growth or the H-degraded fracture toughness K IH [46] ). There are no published analogue studies in support of this approach, although some might be found in the failure analysis literature for carbon steel pressure vessels subject to H-related degradation.…”
Section: Corrosion Processmentioning
confidence: 99%
“…Traditionally, the assessment of the long‐term corrosion performance of the canister has been assessed separately from the structural performance, even though there can be significant interaction between corrosion and mechanical degradation modes for some canister designs. [ 43 ] Various potential corrosion‐mechanical interactions have been considered in TURVA‐2020 for both the copper overpack and the cast iron insert, including: SCC of the copper overpack due to the presence of a suitable species and sufficient tensile stress. Reduction in the creep ductility of copper due to the absorption of hydrogen formed by radiolysis or anaerobic corrosion. Radiation‐induced (γ and neutron) reduction in the ductility of copper. Deformation of the copper overpack due to the formation of expansive cast iron corrosion products (due to corrosion from initially entrained water). Embrittlement of the cast iron insert by the absorption of hydrogen (from the initially entrained water). Embrittlement of cast iron due to neutron irradiation.…”
Section: Canister Evolutionmentioning
confidence: 99%
“…Traditionally, the assessment of the long-term corrosion performance of the canister has been assessed separately from the structural performance, even though there can be significant interaction between corrosion and mechanical degradation modes for some canister designs. [43] Various potential corrosion-mechanical interactions have been considered in TURVA-2020 for both the copper overpack and the cast iron insert, including:…”
Section: Interaction Between Corrosion and Mechanical Loadsmentioning
confidence: 99%